Au/Porous silicon-based sodium borohydride fuel cells - Dzhafarov, T. D.; Lus, C. Oruc; Yuksel, S. Aydin; Caliskan, M.; Yesilkaya, S. S. (WILEY, 2010)
The Au/Porous silicon structure (Au/PS) was developed as hydrogen fuel cell. The use of a porous silicon filled with hydrochloric acid as a proton-conducting membrane and thin gold film as a catalyst in Au/PS/Si fuel cell is demonstrated. The devices were fabricated by first creating 10-20 mu m thick porous silicon layer by anodization etching in a standard silicon wafer and then depositing the gold catalyst film onto the porous silicon. Using sodium borohydride (NaBH4) solution as the fuel, generation of the open-circuit voltage of 0.55 V and the fuel cell peak power density of 13 mW cm(-2) at room temperature was achieved. Moreover production of hydrogen by evolution (out-diffusion) of hydrogen from solid sodium borohydride during thermal annealing at 30-120 degrees C was investigated. Data on the effective diffusion coefficient of the hydrogen in NaBH4 were determined from intensity changes of infrared vibration peaks of B-H bond (2280 and 3280 cm(-1)), as a result of thermal annealing of NaBH4 samples. The relatively high values of the diffusion coefficient of hydrogen, increasing from 1 x 10(-6) cm(2) s(-1) to 2 x 10(-4) cm(2) s(-1) suggest that a thermo-stimulated evolution process can be used for producing hydrogen from NaBH4. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: Au/Porous silicon structure; hydrogen cell; sodium borohydride; hydrogen diffusion; HYDROGEN GENERATION; HYDROLYSIS; Energy & Fuels; Nuclear Science & Technology